ARTIFICIAL RECHARGE FOR SUSTAINABLE GROUNDWATER MANAGEMENT PLAN IN YOGYAKARTA - Nishi Verma; Martin Anda; Yureana Wijayanti (Universitas Trisakti, 2019)
Aim: This study investigates the development of a sustainable groundwater management strategy in Yogyakarta province through groundwater recharge technologies. This study also compares technologies used in the province and the one already implemented in Perth due to its similar nature in site geology and hydrogeology. Methodology and Results: Primary and secondary data were collected and analyzed. Water depth and hydraulic conductivity data were analyzed using permeameter and GIS program. GIS image analysis of water depth and hydraulic conductivity suggested that the placement of potential aquifer recharge sites would be best suited in the north-east part of the province, slightly outside the study area, to provide water for all. Two recharge schemes of an infiltration basin and an injection well with storm water detention tank were proposed. The injection well was decided upon, despite its higher cost, due to the impermeability of soils in Yogyakarta and possible water seepage to the environment. Similar to Perth’s Hartfield park scheme, an injection well would directly bypass these soil layers to recharge the aquifers with rainwater and storm water. Hartfield Park injects 4400 kL of water/year. Conclusion, significance and impact study: The findings of this study indicate aquifer recharge is a possible solution to overcome Yogyakarta’s high abstraction. Further studies recommend that injection well trials are further developed in terms of location, depth and sizing.